The Role of Children's Literature In Developing Character In Globalitation Era - Martina Girsang; Yoana Nazara; Yesika Winata Nababan; Masdelima Purba; Divan Oktavianus Ginting (Lafadz Jaya Publisher, 2023)
This article aims to describe children's literature as character development, it is known that children's literature is considered to be able to shape character effectively because the values contained contain morals that are not conveyed directly, but through stories and metaphors so that the educational process takes place fun and not patronizing. Children's literature is able to support the growth and development of children in terms of emotional, intellectual, imagination, social sense, religious, language development and reading habits.